Pathway Markers for Pro-resolving Lipid Mediators in Maternal and Umbilical Cord Blood: A Secondary Analysis of the Mothers, Omega-3, and Mental Health Study - Mozurkewich, Ellen L.; Greenwood, Matthew; Clinton, Chelsea; Berman, Deborah; Romero, Vivian; Djuric, Zora; Qualls, Clifford; Gronert, Karsten (Frontiers in Pharmacology, 2016)
The omega-3 fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are precursors to immune regulatory and specialized pro-resolving mediators (SPM) of inflammation termed resolvins, maresins, and protections. Evidence for lipid mediator formation in vivo can be gained through evaluation of their 5-lipoxygenase (LOX) and 15-LOX metabolic pathway precursors and downstream metabolites: We performed a secondary blood sample analysis from 60 participants in the Mothers, Omega-3, and Mental Health study to determine whether SPM and SPM precursors are augmented by dietary EPA- and DHA-rich fish oil supplementation compared to soy oil placebo. We also aimed to study whether SPM and their precursors differ in early and late pregnancy or between maternal and umbilical cord blood. We found that compared to placebo supplementation, EPA- and DHA- rich fish oil supplementation increased SPM precursor 17-HDHA concentrations in maternal and umbilical cord blood (P=0.02) We found that the D-series resolvin pathway marker 17-HDHA increased significantly between enrollment and late pregnancy (P=0.049). Levels of both 14-HDHA, a maresin pathway marker, and 17-HDHA were significantly greater in umbilical cord blood than in maternal blood (P<0.001, both).